Earth Observation for enhanced monitoring, evaluation and learning of development programmes - Gouhari, Saeeda (University of Edinburgh School of Geosciences, 2025)
Presented by Saeeda Gouhari (University of Edinburgh) at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025
Keywords: earth observation